Comparative analysis of the safety and efficacy of 1470-nm diode laser enucleation of the prostate and plasmakinetic resection of prostate in the treatment of large volume benign prostatic hyperplasia (>80 ml) - Xiao Xiao; Xiao Maolin; Xiong Tao; Deng Xiaohong; Wang Jinzhong; Tong Wei; Chen Gaoliang; Tang Mengxi (The Aging Male)
Objective To compare the efficacy and safety of 1470-nm diode laser enucleation of the prostate (DiLEP) with that of plasmakinetic resection of the prostate (PKRP) in treating patients with large benign prostatic hyperplasia (BPH > 80ml).Methods The clinical data from 211 cases of BPH (>80 ml) were collected for analysis. The patients were divided into two groups: the PKRP group (n = 118) and the DiLEP group (n = 93), based on the surgical method used.Result The DiLEP group demonstrated significantly lower surgical time (p < 0.001), intraoperative bleeding (p < 0.001), bladder flushing time (p = 0.003), indwelling catheter time (p < 0.005), and length of hospital stay (p = 0.018) compared to the PKRP group. However, the quality of the prostatectomy was significantly higher in the DiLEP group (p = 0.005). The Qmax for the DiLEP group was significantly higher than that of the PKRP group (p < 0.05). Compared to the PKRP group, the incidence of urinary incontinence in the DiLEP group increased significantly 4 weeks post-surgery (p = 0.026), although the need for blood transfusion during surgery was significantly reduced (p = 0.037).Conclusion Both DiLEP and PKRP are safe and effective methods for treating large-volume BPH. However, DiLEP offers advantages such as more thorough glandular resection, shorter surgical time, reduced bleeding, quicker recovery, and fewer complications.